نبیﷺ کےمعجزات پر محمدحسین ھیکل کے شبہات:ایک مطالعہ (Al-Qamar, 2020)
The Holy Prophet (P.B.U.H) was bestowed miracles for three reasons, Firstly, to awaken the consciousness of disbelievers, Secondly, to strengthen the belief of believers, then to punish such rejecters who exceed the limits. As other realities have been being denied, this (miracles of Holy Prophet P.B.U.H) was also denied by some rationalists influenced by the orientalist movement. Muhammad Hussain Heckle is one of those rationalists who denied the miracles of Holy Prophet (P.B.U.H) because of being influenced by orientalist thinking. It seems necessary to view it keeping in mind the basic sources.
Keywords: Miracles of Prophet (P.B.U.H); heckle; Study; Doubts